2019
DOI: 10.1063/1.5097842
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature out-of-plane and in-plane ferroelectricity of two-dimensional β-InSe nanoflakes

Abstract: Two-dimensional (2D) layered semiconductors have shown great application potential in next generation nanoelectronic devices. The ferroelectric and piezoelectric properties of 2D semiconductors are also highly desirable in many applications, such as ferroelectric nonvolatile memory and switch. In the present work, we experimentally demonstrate the simultaneous out-of-plane and in-plane ferroelectricity of β-indium selenide (β-InSe) nanoflakes at room temperature. The polarization switching in the as-prepared β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…InSe displays high mobility (≈10 3 cm 2 /V) because of its marginal effective mass ( m e * = 0.14 m o ) and room-temperature stability with a honeycomb lattice in a Se–In–In–Se covalent configuration . Hu et al , experimentally demonstrated the coexistence of in-plane and out-of-plane ferroelectricity in 7 nm thick InSe flakes and the effect of its polarization on the drain current characteristics. In this study, we utilized the ferroelectric and semiconducting properties of InSe layers used as the channel material for FeFETs integrated with CIPS ferroelectric dielectric.…”
Section: Introductionmentioning
confidence: 99%
“…InSe displays high mobility (≈10 3 cm 2 /V) because of its marginal effective mass ( m e * = 0.14 m o ) and room-temperature stability with a honeycomb lattice in a Se–In–In–Se covalent configuration . Hu et al , experimentally demonstrated the coexistence of in-plane and out-of-plane ferroelectricity in 7 nm thick InSe flakes and the effect of its polarization on the drain current characteristics. In this study, we utilized the ferroelectric and semiconducting properties of InSe layers used as the channel material for FeFETs integrated with CIPS ferroelectric dielectric.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a vertical polarization over 2 pC/m will be reversed upon interlayer translation of a BN bilayer from AB stacking to BA stacking, as shown in Figure a. Such unique FEs exist in many van der Waals bilayers, multilayers, and even bulk structures, including BN, MoS 2 , and InSe (see Figure b), which were later experimentally confirmed in WTe 2 ,, (Figure c), as well as in BN , and InSe bilayer/multilayers. For example, Fei et al measured the vertical polarization of WTe 2 bilayers using the device shown in Figure c, and the result was consistent with theoretical predictions .…”
Section: Data Writingmentioning
confidence: 78%
“…In recent years, some researchers have focused on FMs and FEs in two-dimensional (2D) van der Waals materials with atomic thicknesses. The theoretical designs of FEs in 2D materials date back to 2013, and some have since been experimentally verified, such as IV–VI group compounds (SnTe, SnSe, SnS , ), In 2 Se 3 , van der Waals bilayer/multilayer, distorted 1T MoS 2 , , and Bi 2 O 2 Se. , The discovery of ferroelectricity in CuInP 2 S 6 , and hybrid perovskite bis­(benzylammonium) lead tetrachloride (BA 2 PbCl 4 ) thin layers has also been reported, without related technological predictions. The Curie temperatures of all of these 2D FE systems are above room temperature for practical applications, which remains a challenge for 2D FMs. , Such stability can be attributed to the much larger switching barriers of electric dipoles compared with spins, in general, which may ensure robustness, even in two dimensions.…”
mentioning
confidence: 99%
“…Considering the fundamental mechanism, we believe the phononema observed here may be generalized to other emerging ferroelectric semiconducting materials like β‐InSe and SnTe. [ 44,45 ]…”
Section: Resultsmentioning
confidence: 99%
“…Considering the fundamental mechanism, we believe the phononema observed here may be generalized to other emerging ferroelectric semiconducting materials like β-InSe and SnTe. [44,45] Figure 5a,b summarizes the performances of state-of-the-art photosensors, including Si-based commercial photodiode, commercial APD, commercial PMT, and photodetectors based on emerging two-dimensional (2D) materials reported (for detailed information, see Table S1, Supporting Information). The FSP has a higher R of 3.98 × 10 6 A/W, a lowest NEP of 7.9 × 10 -22 W − Hz 1/2 , and a highest D* of 6.34 × 10 17 Jones (Figure S27, Supporting Information).…”
Section: Ultrasensitive Photodetectionmentioning
confidence: 99%